Effect of winter maize (Zea mays)-based intercropping systems on maize yield, associated weeds and economic efficiency in central Uttar Pradesh - Mishra, Akhilesh (Comunicata Scientiae, 2014)
A field experiment was conducted during winter seasons of 2003-04 and 2004-05 at Kanpur to study the effect of winter maize (Zea mays L.)-based intercropping systems on maize yield, associated weeds and economics under irrigated condition of central Uttar Pradesh. Thirteen maize-based cropping systems, viz. maize sole, potato (Solanum tuberosum L.) sole, mustard [Brassica juncea (L.) Czernj. & Cosson] sole, toria (Brassica campestris var. toria) sole, pea (Pisum sativum L. sensulato) sole, linseed (Linum usitatissimum L.) sole, wheat (Triticum aestivum L. emend. Fiori and Paol.) sole, maize + potato (1:1), maize + mustard (1:1), maize + toria (1:2), maize + pea (1:2), maize + linseed (1:2) and maize + toria (1:2), were tested in randomized block design with three replications. Maize + potato system recorded higher yield attributes and grain yield of maize followed by maize + pea than sole stand of maize. Other intercropping systems reduced the values of yield attributes and grain yield of maize. All the intercropping systems recorded higher maize-equivalent yield, more productivity (kg/ha/day) and significant reduction in weed population and weed dry-biomass than sole cropping of maize. Among the intercropping systems, maize + potato showed significantly higher maize-equivalent yield (13.8 tonnes/ha), productivity (98.51 kg/ha/day), land-equivalent ratio (2.13), monetary returns (Rs 75,069/ha), monetary-equivalent ratio (1.66), monetary efficiency (Rs 536.2/ha/day), relative value total (2.76) and relative net returns (1.91) followed by maize + pea, however significantly lower values of these were associated with maize + toria. Maize + pea recorded the lowest weed population, weed dry-biomass and highest weed-control efficiency.